2016
DOI: 10.1016/j.neo.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Glucose-Regulated Protein 78 in Metastatic Cancer Cells Is Necessary for Lung Metastasis Progression

Abstract: Metastasis is the cause of more than 90% of all cancer deaths. Despite this fact, most anticancer therapeutics currently in clinical use have limited efficacy in treating established metastases. Here, we identify the endoplasmic reticulum chaperone protein, glucose-regulated protein 78 (GRP78), as a metastatic dependency in several highly metastatic cancer cell models. We find that GRP78 is consistently upregulated when highly metastatic cancer cells colonize the lung microenvironment and that mitigation of GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
1
38
0
2
Order By: Relevance
“…28 When treated in combination with gemcitabine, sensitivity to cytotoxic drugs was restored in drug-resistant PDAC cells and increased cell death over gemcitabine treatment alone. In another independent study of an ex vivo lung metastases model, IT-139 targeting GRP78 in metastatic osteosarcoma cells saw a decrease in tumour burden after treatment 29. Combination in vivo studies with cisplatin, 5-FU, oxaliplatin and vemurafenib all show increased anti-tumour efficacy in xenograft colorectal, lung23 and melanoma models (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
“…28 When treated in combination with gemcitabine, sensitivity to cytotoxic drugs was restored in drug-resistant PDAC cells and increased cell death over gemcitabine treatment alone. In another independent study of an ex vivo lung metastases model, IT-139 targeting GRP78 in metastatic osteosarcoma cells saw a decrease in tumour burden after treatment 29. Combination in vivo studies with cisplatin, 5-FU, oxaliplatin and vemurafenib all show increased anti-tumour efficacy in xenograft colorectal, lung23 and melanoma models (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
“…We do know that in the early stages of metastatic lung colonization, disseminated cancer cells experience a variety of cellular stresses (eg, redox/ endoplasmic reticulum stress) that threaten their survival in the distant microenvironment. 49,[54][55][56][57][58][59] However, the clinical relevance of these potential vulnerabilities in patients has yet to be determined. [50][51][52] Animal studies using well-characterized xenograft models of metastatic OS 53 have identified a number of molecular pathways important for metastatic progression.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] Animal studies using well-characterized xenograft models of metastatic OS 53 have identified a number of molecular pathways important for metastatic progression. 49,[54][55][56][57][58][59] However, the clinical relevance of these potential vulnerabilities in patients has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…[109][110][111] The combination of the two metal-based compounds exceeds the efficacy of each complex applied as monotherapy. [42] A phase I clinical trial www.advancedsciencenews.com www.advtherap.com including 46 patients with advanced solid tumors concluded (also based on related in vitro studies when combined, for example, with gemcitabine in endoplasmic reticulum chaperone glucose regulated protein 78 [GRP78] chemoresistant PDAC cells) [113][114][115] that (N)KP1339 could be beneficial in combination therapies with agents that cause hematological toxicity. A combination of NAMI-A and cisplatin was previously shown to result in additive interactions in an in vivo MCa mammary carcinoma model.…”
Section: Rapta-c Versus Kp1019/(n)kp1339 and Nami-amentioning
confidence: 99%
“…[118] One example of a terminated phase I clinical trial involved a study to evaluate the efficacy of vorinostat, a histone deacetylase inhibitor, in combination with fluorouracil and leucovorin. [114,115] Furthermore, patients diagnosed with metastatic colorectal carcinoma and previously treated with other medications were enrolled to the phase II clinical trial evaluating the activity of two drugs applied in combination, namely the chemotherapeutic 5azacitidine administered subcutaneously (day 1-5 and 8-10) and entinostat, which is a HDAC class 1 inhibitor in clinical evaluation specifically deactivating Treg cells, administered orally (day 3 and 10). [32] A secondary phase II trial evaluating differential treatment scheduling administering two doses of vorinostat in the same combination in pre-treated metastatic colorectal carcinoma patients failed as well.…”
Section: Rapta-c and Histone-targeting Drugsmentioning
confidence: 99%